2013
DOI: 10.1007/s00417-013-2513-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disc margin to fovea distance and central visual field defect in normal tension glaucoma

Abstract: Eyes with a shorter DFD should be monitored carefully because central VF involvement appears to be related to shorter DFD in NTG patients with mild VF defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…When comparing the results obtained in Knaapi´s study and the findings of our investigation, one has to take into account the marked difference between both studies in the age and in the background of the study participants. Lee and colleagues measured the distance between the temporal optic disc margin to the fovea distance in 88 patients with normal-tension glaucoma [ 8 ]. They found that in patients with a sparing of the central field the disc margin-fovea distance (3.88 ± 0.28 mm) was longer ( P = 0.002) than in the group with glaucomatous central visual field loss (3.64 ± 0.40 mm) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the results obtained in Knaapi´s study and the findings of our investigation, one has to take into account the marked difference between both studies in the age and in the background of the study participants. Lee and colleagues measured the distance between the temporal optic disc margin to the fovea distance in 88 patients with normal-tension glaucoma [ 8 ]. They found that in patients with a sparing of the central field the disc margin-fovea distance (3.88 ± 0.28 mm) was longer ( P = 0.002) than in the group with glaucomatous central visual field loss (3.64 ± 0.40 mm) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, Knaapi and associates did not find significant associations between the disc-fovea distance and refractive error (or axial length), although one child with axially high myopia had an above-average disc-fovea distance of 6.35 mm. Lee and colleagues measured the distance between the temporal optic disc margin to the fovea distance in 88 patients with normal-tension glaucoma [ 40 ]. They found that in patients with a sparing of the central field the disc margin-fovea distance (3.88 ± 0.28 mm) was longer (P = 0.002) than in the group with glaucomatous central visual field loss (3.64 ± 0.40 mm).…”
Section: Discussionmentioning
confidence: 99%
“…They characterize the position of the optic nerve head in relationship to the fovea (Mok & Lee 2002;Rohrschneider 2004;Jehtani et al 2010;Jonas et al 2011a;van de Put et al 2013;Shin et al 2013;Choi et al 2014;Lee et al 2014). They characterize the position of the optic nerve head in relationship to the fovea (Mok & Lee 2002;Rohrschneider 2004;Jehtani et al 2010;Jonas et al 2011a;van de Put et al 2013;Shin et al 2013;Choi et al 2014;Lee et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The optic disc-fovea distance (DFD) and optic disc-fovea angle (DFA) are important landmarks of the posterior fundus. They characterize the position of the optic nerve head in relationship to the fovea (Mok & Lee 2002;Rohrschneider 2004;Jehtani et al 2010;Jonas et al 2011a;van de Put et al 2013;Shin et al 2013;Choi et al 2014;Lee et al 2014). The DFD can be of importance as an anatomical measure of the posterior fundus, and the DFA influences the position of the perimetric blind spot in spatial relationship to the visual centre.…”
Section: Introductionmentioning
confidence: 99%